Participación y regularización en el barrio Puertas del Sol / nororiente de Quito. - Aguilar Jiménez, Santiago David (2017)
The main object of this current work of systematization is the participation of the neighborhood organization after process of regularization in Puertas del Sol. Through this systematization, we can determine how to improve the life conditions of a neighborhood, which was called outlying and with the support and training of the bases and neighborhood leaders, they promoted the regularization process, obtained the individual ownership, recovered public space with the Puertas del Sol Ecological Park building and achieved the road infrastructure of the main avenue. All this work generates better conditions for the citizens of this district and creates a model of neighborhood development. The impacts that produce the participation process after neighborhood regularization are mainly: economic, educational, social and cultural. Economic impact allowed associative processes with respect to popular and solidarity economy; it means people of Barrio Puertas del Sol built family organic orchards and they get economic resources with them. Educational impact enables child, teenagers and young people to move easily to their educational institutions because roads and the public transportation enhanced. Social impact affected positively to the families of the Puertas del Sol neighborhood. When they are and feel legal owners of their properties, they feel peace and safety for their families because these improvements avoid members family migration (internal and external) and generate the opposite effect, people of Puertas del Sol neighborhood work hardly on their grounds and produce enough money to cover the payments of the basic services. Cultural effects help people to feel identified and proud of living in the Puertas del Sol neighborhood. Nowadays, they live in a worthy place, free pollution and green places, instead of calling their neighborhood as “the dump”.